Hemodynamic and genetic analysis in children with idiopathic, heritable, and congenital heart disease associated pulmonary arterial hypertension - Pfarr, Nicole; Fischer, Christine; Benjamin, Nicola; Becker-Grünig, Tabea; López-González, Vanesa; Gorenflo, Matthias; Hager, Alfred; Hinderhofer, Katrin; Miera, Oliver; Nagel, Christian; Schranz, Dietmar; Grünig, Ekkehard (Respiratory research, 2013)
Background: Aim of this prospective study was to compare clinical and genetic findings in children with idiopathic or heritable pulmonary arterial hypertension (I/HPAH) with children affected with congenital heart defects associated PAH (CHD-APAH). Methods: Prospectively included were 40 consecutive children with invasively diagnosed I/HPAH or CHD-APAH and 117 relatives. Assessment of family members, pedigree analysis and systematic screening for mutations in TGFß genes were performed. Results: Five mutations in the bone morphogenetic protein type II receptor (BMPR2) gene, 2 Activin A receptor type II-like kinase-1 (ACVRL1) mutations and one Endoglin (ENG) mutation were found in the 29 I/HPAH children. Two mutations in BMPR2 and one mutation in ACVRL1 and ENG, respectively, are described for the first time. In the 11 children with CHD-APAH one BMPR2 gene mutation and one Endoglin gene mutation were found. Clinical assessment of relatives revealed familial aggregation of the disease in 6 children with PAH (HPAH) and one CHD-APAH patient. Patients with mutations had a significantly lower PVR. Conclusion: Mutations in different TGFß genes occurred in 8/29 (27.6%) I/HPAH patients and in 2/11 (18.2%) CHD-APAH patients and may influence the clinical status of the disease. Therefore, genetic analysis in children with PAH, especially in those with I/HPAH, may be of clinical relevance and shows the complexity of the genetic background.
Gesehen am 20.01.2022